2022
DOI: 10.3389/fimmu.2022.1018701
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of immune microenvironment infiltration and m6A regulator-mediated RNA methylation modification patterns in osteoarthritis

Abstract: BackgroundFew studies have been reported the potential role of N6-methyladenosine (m6A) modification in osteoarthritis (OA). We investigated the patterns of m6A modification in the immune microenvironment of OA.MethodsWe evaluated the m6A modification patterns based on 22 m6A regulators in 139 OA samples and systematically associated these modification patterns with immune cell infiltration characteristics. The function of m6A phenotype-related differentially expressed genes (DEGs) was investigated using gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…ssGSEA calculates the individual enrichment scores of samples and gene sets through the "GSVA" and "GSEABase" R packages. The gene set of in ltrating immune cells included both immune-enhancing and immunosuppressive cells 21,22 . The CIBERSORT algorithm (https://cibersort.stanford.edu/) was used to estimate the relative abundance of immune cells in each sample 23 .…”
Section: Methodsmentioning
confidence: 99%
“…ssGSEA calculates the individual enrichment scores of samples and gene sets through the "GSVA" and "GSEABase" R packages. The gene set of in ltrating immune cells included both immune-enhancing and immunosuppressive cells 21,22 . The CIBERSORT algorithm (https://cibersort.stanford.edu/) was used to estimate the relative abundance of immune cells in each sample 23 .…”
Section: Methodsmentioning
confidence: 99%
“…Recently study revealed that m6A was proved involved in OA progression by regulating immune responses [ 88 ]. Evidence found that IGFBP1 and RBM15B were strongly correlated with infiltrating immunocytes [ 89 ], YTHDF2 was positively related with regulatory T cells, IGFBP2 was negatively associated with dendritic cells [ 90 ], and IGF2BP3 upregulation promoted macrophage M1 polarization in OA [ 91 ].…”
Section: M6a and Skeletal System Diseasementioning
confidence: 99%
“…Alterations in RNA methylation are also observed in age-related diseases and, interestingly, m 6 A modifications have been implicated in the regulation of different biological processes associated with ageing, including inflammation ( 117 ). Often, these alterations derive from a misbalanced regulation of m 6 A regulatory factors.…”
Section: Metabolism and Epigenetics Deregulation In Diseasementioning
confidence: 99%